Improvement of the system of state regulation and support of small business in volatile economic environment - S. K. Eshugova; S. K. Khamirzova (Новые технологии)
The article discusses the need to form an effective system of state regulation and support of small businesses in order to implement effective measures to stimulate their development. In addition, the article examines the effectiveness of implemented state measures for the development of small businesses in terms of their functional and economic performance, outlines fundamental principles for their implementation.